1987
DOI: 10.1002/em.2860090403
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide: Induction of heritable translocations in male mice

Abstract: Acrylamide (AA), known to induce dominant lethals in male rodents, was studied in the mouse heritable translocation test by using intraperitoneal injections on 5 consecutive days. Matings on days 7-10 following the last injection yielded a high frequency of translocation carriers in the F1 male population, which demonstrated that acrylamide is an effective inducer of translocations in postmeiotic germ cells. As an inducer of both dominant lethals and heritable translocations in late spermatids and early sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…The frequencies of dead implants per female are increased with both modes of exposure during the first three mating intervals, which represent sperm and late spermatids. This pattern of sensitivity is in accord with previous publications (Shelby et al, 1986(Shelby et al, , 1987Smith et al, 1986, Holland et al, 1999. The dominant lethal effects are illustrated in Fig.…”
Section: Statisticssupporting
confidence: 80%
See 1 more Smart Citation
“…The frequencies of dead implants per female are increased with both modes of exposure during the first three mating intervals, which represent sperm and late spermatids. This pattern of sensitivity is in accord with previous publications (Shelby et al, 1986(Shelby et al, , 1987Smith et al, 1986, Holland et al, 1999. The dominant lethal effects are illustrated in Fig.…”
Section: Statisticssupporting
confidence: 80%
“…Using flow cytometer-based analyses, it was demonstrated that the dose-response relationship for AA-induced micronuclei in mouse bone marrow cells was linear down to low single doses of 1-30 mg/kg AA applied by intraperitoneal (ip) injection (Abramsson-Zetterberg, 2003). In rodent germ cells, dominant lethal mutations and heritable translocations were induced by ip injection with AA in late spermatids and sperm (Adler, 1990;Shelby et al, 1986Shelby et al, , 1987Smith et al, 1986). Analysis of structural chromosome aberra-tions in one-cell embryos after paternal AA-treatment was performed using conventional and molecular techniques (Pacchierotti et al, 1994;Marchetti et al, 1997).…”
mentioning
confidence: 99%
“…Favor and Shelby (2005) reviewed seven published studies that assessed the effectiveness of AA and GA in inducing transmitted reciprocal translocations or gene mutations in the mouse. Results indicated an increase in the frequency of translocation carriers in offspring following paternal exposure to AA or GA in spermatid and spermatozoa (Shelby et al, 1987;Adler, 1990;Adler et al, 1994Adler et al, , 2004Generoso et al, 1996). Even the dose of 50 mg AA/kg b.w.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The National Toxicology Program (NTP) has taken a prominent role in the identification of genetic hazards in the environment and in the acquisition ofdata that are used by regulatory agencies in assessing genetic risks to human health. For example, NTP-sponsored germ-cell mutagenesis studies have been responsible for the identification of acrylamide as a reproductive hazard (21)(22)(23), and dose-response and dose-rate data on ethylene oxide have been used by the EPA in their hazard assessment efforts. The evaluation of various aspects of germ-cell mutagenesis such as dose, dose rate, sex, and strain effects; investigations of mutation induction in cells such as oocytes and zygotes; and identification of models of human genetic diseases such as those for j-thalassemia (26,27) and carbonic anhydrase-2 deficiency (28) are among the contributions made to the understanding of mammalian germ-cell mutagenesis.…”
Section: The Human Health Issuementioning
confidence: 99%